REGULATION OF AUXIN COMPOUND IN IN VITRO CULTURE OF GO POTATO SEEDS PRODUCTION - Misbah Ruhiyat; Syarif Husen; Nurina Farahiyah (UNEJ e-Proceeding, 2017)
Auxin has a role in the growth and development of plant roots. This research examinedthe effect of IAA and NAA growth regulators in in vitro culture of potato. Employing grouprandomized design, this research was conducted in "Plant improvement" in vitro laboratoryof FPP UMM. The results showed that the auxin compound which served as a growthregulator substance had a significant effect on shoot and root induction of in vitro potato. IAAcompound was faster in inducing roots compared to NAA, but IAA could also reduce thenumber of roots. IAA addition could strengthen the plant during acclimatization.